Spain : Financial Sector Assessment Program; Detailed Assessment of the CPSS Core Principles for Systemically Important Payment Systems. (IMF Staff Country Reports; Country Report ;, 2006)
The assessment of the Systemically Important Payment System (SIPS) in Spain against the Committee on Payment and Settlement Systems (CPSS) Core Principles was undertaken as part of the Financial Sector Assessment Program (FSAP). It assesses the Observance of Core Principles for Systemically Important Payment Systems (CPSIPS) of the IMF and the World Bank. It reviews the discussions of the staffs of the Banco de Espana (BE) and commercial banks. It analyzes the self assessment by the BE and the assessment of the Euro Large-Value Payment System against the core principles published by the European Central Bank.